Preparation method of spherical large-particle cobaltosic oxide

By adding surfactant to the cobalt salt solution and controlling the stirring speed and pH, a large-particle spherical cobalt carbonate precursor was prepared, and a high-pressure cobalt tetroxide was obtained through one sintering, which solved the problems of cumbersome operation, time-consuming and low electrochemical performance in the prior art, and achieved the effects of shortening synthesis time, reducing energy consumption and improving electrochemical performance.

CN119683696APending Publication Date: 2025-03-25ANHUI HANRUI NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510026797.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing liquid phase precipitation-thermal decomposition method to prepare large-grain cobalt tetroxide is cumbersome, time-consuming, and labor-intensive. In addition, local concentrations are uneven in the later stage of growth, which easily leads to a reduction in electrochemical performance. The calcination process requires secondary sintering, high energy consumption and low equipment utilization.

Method used

The size and morphology of the crystal nucleus are changed by adding surfactant to the cobalt salt solution, and the morphology of the primary particles is controlled with the appropriate stirring speed and reaction pH, forming a large-grain spherical cobalt carbonate precursor, and obtaining highly compacted cobalt tetroxide through primary sintering.

Benefits of technology

It effectively shortens the synthesis time, avoids the generation of small particles, simplifies the sintering process, reduces energy consumption, and improves the tap density and electrochemical properties of cobalt tetroxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683696A_ABST
    Figure CN119683696A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of spherical large-particle cobaltosic oxide, which comprises a cobalt carbonate synthesis stage and a thermal decomposition stage, and comprises the following steps: firstly synthesizing hexagonal-prism-shaped cobalt carbonate through structural regulation in the cobalt carbonate synthesis stage, and disorderly arranging the hexagonal-prism-shaped cobalt carbonate to form a sphere-like framework; converting the primary particles into blocky structures, gradually stacking and growing to form a compact large-particle-size cobalt carbonate precursor, and finally calcining for one time to form large-particle-size cobaltosic oxide. By regulating and controlling the structure of the cobalt carbonate, the problems that the process for preparing the large-particle cobaltosic oxide through an existing cobalt carbonate precipitation-thermal decomposition technology is tedious in operation, long in time, prone to nucleation, prone to cracking and the like are effectively solved, and the prepared cobaltosic oxide is uniform in particle size distribution, high in tap density and high in stability; and the development requirements of the lithium cobalt oxide positive electrode material with high volume energy density are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery lithium cobalt oxide positive electrode material precursor preparation, in particular to a method for preparing spherical large-particle cobalt oxide. Background Art

[0002] Lithium cobalt oxide positive electrode material has the advantages of high voltage, stable discharge, and simple production process. It is the lithium-ion battery positive electrode material with the largest share in the current 3C digital product market. In recent years, with the continuous enrichment of the functions of electronic products, more and larger components are continuously added to the products, which seriously squeezes the empty volume and mass energy density of lithium-ion batteries. Cobalt oxide has high crystal field stabilization energy and good specific capacity, and is considered to be the most promising raw material for lithium cobalt oxide production. The preparation of large-particle cobalt oxide is conducive to improving the compaction density of LCO materials.

[0003] At present, the main method that has been realized in industrial production is liquid phase precipitation-thermal decomposition method, which mainly uses large-particle cobalt carbonate as cobalt salt intermediate and adopts calcination method to prepare Co3O4 powder. In the process of wet precipitation, in order to maintain the growth rate of cobalt carbonate and avoid the generation of small particles, patent CN105399148A needs to be divided into several kettles, and the divided kettle materials need to be transferred to the aging tank; in the calcination stage, in order to prevent the particles from breaking, two stages of sintering are required, namely low-temperature pre-sintering and high-temperature sintering. This preparation process is cumbersome, time-consuming, and labor-intensive. In addition, the uneven local concentration in the late growth stage is prone to small particles, which leads to reduced electrochemical performance. Secondly, the calcination process often requires secondary sintering, which has high energy consumption and low equipment utilization. Summary of the invention

[0004] The present invention aims at the problems that the existing liquid phase precipitation-thermal decomposition method for preparing large-particle cobalt tetroxide is complicated, time-consuming, and labor-intensive, and the local concentration is uneven in the late growth stage, and small particles are easily generated, resulting in reduced electrochemical performance. Secondly, the calcination process often requires secondary sintering, and the energy consumption is high, and the equipment utilization rate is low. A method for preparing spherical large-particle cobalt tetroxide is provided. The method changes the size and morphology of the crystal nucleus by adding a surfactant to a cobalt salt solution, and then effectively controls the morphology of the primary particles in combination with the corresponding stirring speed and reaction pH, and changes the conventional preparation process of large-particle cobalt tetroxide; first, a hexagonal spherical skeleton is synthesized through ellipsoidal primary particles, and then a large-particle spherical cobalt carbonate precursor is prepared through dense packing growth of blocky primary particles, and finally a high-tapped cobalt tetroxide can be obtained by sintering once. The present invention does not require multiple separate kettle operations, which can effectively shorten the synthesis time and reduce or even avoid the generation of small particles during wet precipitation.

[0005] The method for preparing spherical large-particle cobalt oxide provided by the present invention comprises the following steps:

[0006] ① Prepare ammonium bicarbonate solution A and ammonium bicarbonate solution B, add ammonium bicarbonate solution A into the reaction kettle to cover the bottom stirring paddle as the bottom liquid;

[0007] ② adding a surfactant to the cobalt salt solution to obtain a cobalt salt mixed solution, adding the cobalt salt mixed solution and the ammonium bicarbonate solution B of step ① into a reactor in parallel, reacting under the conditions of pH 8 to 8.4 and a stirring speed of 200 to 400 r / min to generate ellipsoidal primary particles which gradually accumulate to form hexagonal prisms of regular shape, and the hexagonal cobalt carbonate is randomly arranged to form a spherical skeleton;

[0008] ③ Continue to introduce the cobalt salt composite solution and ammonium bicarbonate solution B into the reactor, adopt an intermittent process, react under the conditions of pH 7.1-7.5 and stirring speed 500-700r / min, so that the primary particles are transformed into blocks and adsorbed on the hexagonal prism skeleton to continue to grow and gradually form large particles of spherical cobalt carbonate, until the preset particle size is reached, and then filtered, washed, and dried in sequence to obtain a cobalt carbonate precursor with a dense internal structure and no obvious pores;

[0009] ④ Place the cobalt carbonate precursor of step ③ into a box-type atmosphere furnace and sinter once to obtain the target product.

[0010] As a preferred embodiment of the present invention, in step ①, the concentration of ammonium bicarbonate solution A is 30-70 g / L, and the concentration of ammonium bicarbonate solution B is 160-280 g / L.

[0011] As a preferred embodiment of the present invention, the cobalt salt solution in step ② is a mixture of one or more of a cobalt chloride solution, a cobalt sulfate solution, and a cobalt nitrate solution, wherein the cobalt content is 80-140 g / L; the surfactant is citric acid, and the mass of the citric acid accounts for 1-2% of the mass of cobalt in the cobalt salt solution; the molar ratio of the cobalt salt mixture to the ammonium bicarbonate solution B is 0.25-0.35; the reaction time is 2-4 h, the reaction temperature is 40-60° C., and the particle size of the spherical skeleton structure cobalt carbonate is 4-6.5 μm.

[0012] As a preferred embodiment of the present invention, the molar ratio of the cobalt salt mixed solution to the ammonium bicarbonate solution B in step ③ is 0.43-0.48; the preset particle size is 16-20 μm; the reaction temperature is 40-60° C., and the synthesis time is 75-90 h.

[0013] As a preferred embodiment of the present invention, in step ④, the heating rate of the box-type atmosphere furnace is 5°C / min, the sintering temperature is 700-750°C, and the sintering time is 2-4h.

[0014] The beneficial effects of the present invention are as follows:

[0015] The present invention creatively synthesizes high-density spherical large-particle cobalt tetroxide by regulating the structure of the precursor cobalt carbonate. First, a large-sized hexagonal spherical skeleton is quickly synthesized in the early stage of the reaction, and then a large-particle dense spherical cobalt carbonate precursor is formed through dense packing growth of blocky primary particles. Finally, the cobalt carbonate precursor is sintered once to obtain the cobalt tetroxide product, avoiding the multiple split-kettle operations in the prior art, effectively shortening the synthesis time, and solving the problem of small particles in the cobalt carbonate synthesis process. Compared with the prior art, the sintering procedure is simpler, the sintering time is further shortened, and the energy consumption is further reduced. The cobalt tetroxide obtained after calcination has no cracking phenomenon and has a higher tap density, and its tap density is 2.6g / cm 3 above. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 SEM images of the samples of Example 1: (a) - first stage, (b) - early stage of the second stage, (c) - cobalt carbonate, (d) - cobalt trioxide.

[0017] Figure 2 These are SEM images of samples from Example 2: (a) - first stage, (b) - early second stage, (c) - cobalt carbonate, (d) - cobalt tetroxide.

[0018] Figure 3 These are SEM images of samples from Example 3: (a) - first stage, (b) - early second stage, (c) - cobalt carbonate, (d) - cobalt trioxide.

[0019] Figure 4 SEM images of the samples of Comparative Example 1: (a) - first stage, (b) - early stage of the second stage, (c) - cobalt carbonate, (d) - cobalt tetroxide. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with embodiments and comparative examples. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0021] Embodiment 1:

[0022] Preliminary preparation: prepare a cobalt sulfate solution with a cobalt content of 120 g / L and add 2 g / L of citric acid to obtain a cobalt salt mixture, prepare 50 g / L of ammonium bicarbonate solution A and 220 g / L of ammonium bicarbonate solution B respectively, add ammonium bicarbonate solution A into the reactor to cover the bottom stirring paddle as the bottom liquid;

[0023] The first stage: the cobalt salt flow rate is 1L / h, the cobalt salt mixed solution and ammonium bicarbonate solution B are added to the reactor in a molar ratio of 0.3, the reaction temperature is 50°C, the stirring speed is 300r / min, the pH is controlled at 8.2-8.4, the synthesis time is 4h, and D is formed. 50 It is a 6.5μm hexagonal spherical skeleton;

[0024] The second stage: the cobalt salt flow rate is 2L / h, the molar ratio of the cobalt salt composite solution and the ammonium bicarbonate solution B is 0.45, the stirring speed is controlled at 600r / min, the pH gradually decreases and stabilizes in the range of 7.2-7.4, the primary particles are transformed into blocks and adsorbed on the hexagonal skeleton to continue to grow and gradually form large particles of spherical cobalt carbonate, the synthesis time is 90h, D 50 When the particle size reaches 18.9 μm, the synthesis is stopped, and the mixture is washed and dried after aging.

[0025] Calcination: A box-type atmosphere furnace was used with a heating rate of 5°C / min and a carbon sintering temperature of 700°C. Large particles of cobalt trioxide were obtained by calcining for 3 hours.

[0026] The different stages of the product generation process are as follows Figure 1 As shown, Figure 1 It can be clearly seen that the primary particles are hexagonal, and their disordered arrangement forms a spherical skeleton structure. The subsequently generated blocky particles are adsorbed on the spherical skeleton and continue to grow, eventually generating cobalt carbonate with a denser surface and higher sphericity. The surface of the cobalt oxide obtained after calcining the cobalt carbonate forms uniform pores without cracking.

[0027] Embodiment 2:

[0028] Preliminary preparation: prepare a cobalt sulfate solution with a cobalt content of 140 g / L and add 3 g / L of citric acid to obtain a cobalt salt mixture, prepare 70 g / L of ammonium bicarbonate solution A and 280 g / L of ammonium bicarbonate solution B respectively, add the ammonium bicarbonate solution A into the reactor to cover the bottom stirring paddle as the bottom liquid;

[0029] The first stage: the cobalt salt flow rate is 1L / h, the cobalt salt mixed solution and ammonium bicarbonate solution B are added to the reactor in a molar ratio of 0.35, the reaction temperature is 40°C, the stirring speed is 400r / min, the pH is controlled at 8.0-8.2, the synthesis time is 2h, and D is formed. 50 It is a 4μm hexagonal spherical skeleton;

[0030] The second stage: the cobalt salt flow rate is 2L / h, the molar ratio of the cobalt salt composite solution and the ammonium bicarbonate solution B is 0.48, the stirring speed is controlled at 500r / min, the pH gradually decreases and stabilizes in the range of 7.1-7.3, the primary particles are transformed into blocks and adsorbed on the hexagonal skeleton to continue to grow and gradually form large particles of spherical cobalt carbonate, the synthesis time is 75h, D 50 When the particle size reaches 16.8 μm, the synthesis is stopped, and the mixture is washed and dried after aging.

[0031] Calcination: A box-type atmosphere furnace was used with a heating rate of 5°C / min and a carbon sintering temperature of 700°C. Large particles of cobalt trioxide were obtained by calcining for 3 hours.

[0032] The different stages of the product generation process are as follows Figure 2 As shown, Figure 2 It can be clearly seen that the primary particles are hexagonal and form a spherical skeleton structure. Subsequently, the primary particles transform and continue to fill the defects of the spherical skeleton, and finally form cobalt carbonate with a certain sphericity. The surface pores of the cobalt tetroxide obtained after calcining the cobalt carbonate are uniform, and no cracking occurs.

[0033] Embodiment 3:

[0034] Preliminary preparation: prepare a cobalt sulfate solution with a cobalt content of 80 g / L and add 1 g / L of citric acid to obtain a cobalt salt mixture, prepare 30 g / L of ammonium bicarbonate solution A and 160 g / L of ammonium bicarbonate solution B respectively, add the ammonium bicarbonate solution A into the reactor to cover the bottom stirring paddle as the bottom liquid;

[0035] The first stage: the cobalt salt flow rate is 1L / h, the cobalt salt mixed solution and ammonium bicarbonate solution B are added to the reactor in a molar ratio of 0.25, the reaction temperature is 60℃, the stirring speed is 200r / min, the pH is controlled at 8.3-8.4, the synthesis time is 3h, and D is formed. 50 It is a 4.3μm hexagonal spherical skeleton;

[0036] The second stage: the cobalt salt flow rate is 2L / h, the molar ratio of the cobalt salt composite solution and the ammonium bicarbonate solution B is 0.43, the stirring speed is controlled at 700r / min, the pH gradually decreases and stabilizes in the range of 7.3-7.5, the primary particles are transformed into blocks and adsorbed on the hexagonal skeleton to continue to grow and gradually form large particles of spherical cobalt carbonate, the total synthesis time is 81h, D 50 When the particle size reaches 18.2 μm, the synthesis is stopped, and the mixture is washed and dried after aging.

[0037] Calcination: A box-type atmosphere furnace was used with a heating rate of 5°C / min and a carbon sintering temperature of 700°C. Large particles of cobalt trioxide were obtained by calcining for 3 hours.

[0038] The different stages of the product generation process are as follows Figure 3 As shown, Figure 3 It can be clearly seen that a spherical skeleton is prepared in the first stage, and the defects of the densely packed skeleton are gradually filled in the second stage, and finally spherical large particles of cobalt carbonate are formed. After calcination, the surface pores of cobalt oxide are uniform and no cracks occur.

[0039] Comparative Example 1:

[0040] Compared with Example 1, the temperature of the first stage experiment and the rotation speed and feeding molar ratio of the second stage are different. The specific implementation process is as follows:

[0041] Preliminary preparation: prepare a cobalt sulfate solution with a cobalt content of 120 g / L and add 2 g / L of citric acid to obtain a cobalt salt mixture, prepare 50 g / L of ammonium bicarbonate solution A and 220 g / L of ammonium bicarbonate solution B respectively, add the ammonium bicarbonate solution A into the reactor to cover the bottom stirring paddle as the bottom liquid;

[0042] The first stage: the cobalt salt flow rate is 1L / h, the cobalt salt mixed solution and ammonium bicarbonate solution B are added to the reactor in a molar ratio of 0.3, the reaction temperature is 65℃, the stirring speed is 300r / min, the pH is controlled at 8.3-8.4, the synthesis time is 4h, and D is formed. 50 It is a hexagonal spherical skeleton of 6.92 μm;

[0043] The second stage: the cobalt salt flow rate is 2L / h, the molar ratio of the cobalt salt composite solution and the ammonium bicarbonate solution B is 0.4, the stirring speed is controlled at 300r / min, the pH gradually decreases and stabilizes in the range of 7.5-7.7, the total synthesis time is 40h, D 50 When the particle size reaches 19.6 μm, the synthesis is stopped, and the mixture is washed and dried after aging.

[0044] Calcination: A box-type atmosphere furnace was used with a heating rate of 5°C / min and a carbon sintering temperature of 700°C. Large particles of cobalt trioxide were obtained by calcining for 3 hours.

[0045] The different stages of the product generation process are as follows Figure 4 As shown, Figure 4 It can be clearly seen that the primary particles are also regularly shaped hexagonal prisms, but compared with Examples 1-3, the primary particles in the second stage of the synthesis reaction did not change, and the spherical hexagonal prisms continued to grow. Although the secondary particles generated at this time were also spherical, the surface defects were relatively serious and dense spherical cobalt carbonate could not be formed, resulting in a low tap density. The cobalt oxide columnar structure obtained after calcining cobalt carbonate formed certain pores on the surface, resulting in reduced electrochemical performance.

[0046] Target product physical and chemical index evaluation table

[0047]

[0048] In summary, the wet synthesis stage of the cobalt carbonate precursor includes the first and second stages in Examples 1-3. The synthesis time is 70 to 90 hours to obtain a spherical cobalt carbonate precursor with a particle size of 16 to 20 μm. The surface pores of the cobalt tetroxide obtained by one sintering are uniform and all broken. The results of the physical and chemical index evaluation table show that the cobalt tetroxide prepared by the present invention has a short synthesis time and a tap density of 2.6 g / cm 3 The above is much higher than the tap density of the cobalt oxide in the comparative example; due to the high tap density, the cobalt oxide prepared by the present invention is used as a precursor of the lithium cobalt oxide positive electrode material for lithium ion batteries to further improve the stability, specific capacity and electrochemical performance of the electrode, thereby further improving the overall performance of the battery.

[0049] The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the technical principles of the present invention. These changes, modifications, substitutions and variations should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing spherical large particles of cobalt trioxide, characterized in that: The following steps are involved: ① Prepare ammonium bicarbonate solution A and ammonium bicarbonate solution B, add ammonium bicarbonate solution A into the reaction kettle to cover the bottom stirring paddle as the bottom liquid; ② adding a surfactant to the cobalt salt solution to obtain a cobalt salt mixed solution, adding the cobalt salt mixed solution and the ammonium bicarbonate solution B of step ① into a reaction kettle in parallel, reacting under the conditions of pH 8 to 8.4 and a stirring speed of 200 to 400 r / min to generate cobalt carbonate with a spherical skeleton structure; ③ Continue to introduce the cobalt salt composite solution and ammonium bicarbonate solution B into the reactor, react under the conditions of pH 7.1-7.5 and stirring speed 500-700 r / min until the preset particle size is reached, and then filter, wash and dry to obtain a cobalt carbonate precursor; ④ Place the cobalt carbonate precursor of step ③ into a box-type atmosphere furnace and sinter once to obtain the target product.

2. The preparation method according to claim 1, characterized in that: In the step ①, the concentration of the ammonium bicarbonate solution A is 30-70 g / L, and the concentration of the ammonium bicarbonate solution B is 160-280 g / L.

3. The preparation method according to claim 1, characterized in that: The cobalt salt solution in step ② is a mixture of one or more of a cobalt chloride solution, a cobalt sulfate solution, and a cobalt nitrate solution, wherein the cobalt content is 80 to 140 g / L.

4. The preparation method according to claim 1, characterized in that: In step ②, the surfactant is citric acid, and the mass of the citric acid accounts for 1-2% of the mass of cobalt in the cobalt salt solution.

5. The preparation method according to claim 1, characterized in that: In step ②, the molar ratio of the cobalt salt mixed solution to the ammonium bicarbonate solution B is 0.25 to 0.

35.

6. The preparation method according to claim 1, characterized in that: The reaction time in step ② is 2 to 4 hours, and the reaction temperature is 40 to 60°C.

7. The preparation method according to claim 1, characterized in that: In step ③, the molar ratio of the cobalt salt mixed solution to the ammonium bicarbonate solution B is 0.43 to 0.

48.

8. The preparation method according to claim 1, characterized in that: The preset particle size in step ③ is 16 to 20 μm.

9. The preparation method according to claim 1, characterized in that: In step ③, the reaction temperature is 40-60° C. and the reaction time is 75-90 hours.

10. The preparation method according to claim 1, characterized in that: In the step ④, the sintering temperature is 700-750° C. and the sintering time is 2-4 hours.

Citation Information

Patent Citations

  • Preparation method of large-particle-size and high-density spherical cobalt oxide

    CN105399148A